2008
DOI: 10.1371/journal.pgen.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neural Outgrowth Genes using Genome-Wide RNAi

Abstract: While genetic screens have identified many genes essential for neurite outgrowth, they have been limited in their ability to identify neural genes that also have earlier critical roles in the gastrula, or neural genes for which maternally contributed RNA compensates for gene mutations in the zygote. To address this, we developed methods to screen the Drosophila genome using RNA-interference (RNAi) on primary neural cells and present the results of the first full-genome RNAi screen in neurons. We used live-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 78 publications
(102 reference statements)
5
80
0
Order By: Relevance
“…2013), while Formin‐like protein ( Dmel_CG32138 ) and Dmel_CG17912 are involved in neurogenesis (Sepp et al. 2008; Iyer et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…2013), while Formin‐like protein ( Dmel_CG32138 ) and Dmel_CG17912 are involved in neurogenesis (Sepp et al. 2008; Iyer et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…W e r eported the first full-ge nome RNA interferenc e (RNAi) s creen on Drosophila prim ary neural cells (Sepp , Hong et al 2008). Our study revealed unexpected, e ssential roles in neurite outgrowth for genes representing a wide ran ge of f unctional ca tegories inc luding signa lling m olecules, enzym es, channels, receptors, and cytoskeletal proteins.…”
Section: Body (Research) (A) High-content Image Analysismentioning
confidence: 84%
“…The events that underlie tumorigenesis, tumor progression, and tumor response to conventional therapies each represent excellent targets for selective killing of cancer cells versus normal cells that may be delineated on an siRNA-based screen, although the potential applications of these approaches in neurooncology and neurosurgery may have relevance from both a therapeutic and mechanistic perspective. 38,60 Recent siRNA screens in cancer and disease models have focused on: 1) reversing the cancer phenotype, 2) identifying synthetic lethal targets, 3) developing synergistic drug combinations, and 4) clarifying underlying mechanisms of biological processes (Table 1).…”
Section: Implementing Sirna Screensmentioning
confidence: 99%
“…Function and development of the brain require the coordinated action of numerous genes, but we currently understand the functions of only a small fraction of them. 60 The integration of phenotypic information from genomic and proteomic data sets has revealed many important cellular processes at an unprecedented resolution. 17 There are several such studies in neuroscience that have provided insight into the development and function of the nervous system, including neural outgrowth 60 and identification of kinase clusters that are required for neurite outgrowth and retraction 38 (Table 1).…”
Section: Mechanistic Clarification Of Biological Processesmentioning
confidence: 99%
See 1 more Smart Citation